Assessing the impacts of climate change on women's poverty: A Bolivian case study - Escalante, Luis Enrique; Maisonnave, Helene (Wiley, 2023)
Climate change affects men and women differently, and pre-existing gender disparities may worsen. We use a gendered computable general equilibrium model linked with microsimulations to assess the distributive effects of climate change in Bolivia. Two scenarios are evaluated. The first scenario addresses capital and land damages, while the second analyses the decrease in agricultural production yields. We find that both scenarios have negative impacts on the Bolivian economy. The scenarios drive down employment and increase the burden of domestic work, especially for women. Furthermore, both simulations reveal negative impacts on poverty, with women in rural areas being the most affected.